Tunnel Inspection Review: Normative Practices and Non-Destructive Method Advancements for Tunnels with Concrete Cover - Bernardo Lopes Poncetti; Dianelys Vega Ruiz; Leandro Silva de Assis; Lucas Bellini Machado; Tiago Borges da Silva; Ayokunle Adewale Akinlalu; Marcos Massao Futai (Applied Mechanics)
Guaranteeing tunnel integrity is an important issue for several countries worldwide. Due to the continuous increase in the number of tunnels, as well as the aging of old tunnels, several countries and companies have created manuals to standardize tunnel inspection and assessment. Most manuals still specify just visual procedures for tunnel inspection; however, because of underground conditions, the structural system of tunnels is often accessible only by one side, thus posing difficulties to the accurate evaluation of the structural conditions of the tunnel using only visual inspection. A possibility to improve the effectiveness of tunnel inspection is the use of non-destructive testing (NDT), which will assist in obtaining information about the inner condition behind the tunnel wall. The current advancements in the NDT methods allow them to be employed in all the different kinds of inspections (initial, routine, special inspection) suggested by the manuals. Therefore, in an attempt to help in the decision about the application of each method, this work provides an overview of some international practices for tunnel inspections and shows a review of different NDT methods (traditional and new methods) applied to tunnel inspections. Furthermore, this study describes their workability, advantages, and capability, and classifies the best fitting of each in the inspection procedures.